Improved Osteogenesis by Mineralization Combined With Double-Crosslinked Hydrogel Coating for Proliferation and Differentiation of Mesenchymal Stem Cells - Ma, Yiqun; You, Yuwang; Cao, Lu; Liang, Bing; Tian, Bo; Dong, Jian; Lin, Hong (Frontiers in Bioengineering and Biotechnology, 2021)
In consideration of the improving the interface problems of PLLA that hindered biomedical use, surface coatings has been explored as an appealing strategy in establishing the multi-functional coating for osteogenesis. Though the layer by layer (LBL) coating developed, few studies have applied double crosslink hydrogels in this technique. In this research, we established a bilayer coating with double crosslink hydrogels (alginate-GelMA) containing BMP-2 proteins (alginate-GelMA/HA/BMP-2) which displayed great biocompatibility and osteogenesis. The characterization of the coating showed the improved the properties and enhanced the wettability of the native PLLA. To evaluate the biosafety and inductive ability of osteogenesis, the behavior (viability, adherence, and proliferation) and morphology of hBMSCs on the bilayer coatings were tested by multiple exams. The satisfactory function of osteogenesis was verified in bilayer coatings. We found the best ratios between GelMA and alginate for biological applications. The Alg70-Gel30 and Alg50-Gel50 group facilitated the osteogenic transformation of hBMSCs. In brief, alginate-GelMA/HA/BMP-2 could increase the hBMSCs’ early transformation of osteoblast-lineage and promote the osteogenesis of bone defect, especially the outer hydrogel layer as Alg70-Gel30 and Alg50-Gel50.